Application of Tabu Search Algorithm in Job Shop Scheduling - Betrianis, Betrianis; Aryawan, Putu Teguh (UI Scholars Hub, 2003)
Application of Tabu Search Algorithm in Job Shop Scheduling. Tabu Search is one of local search methods which is used to solve the combinatorial optimization problem. This method aimed is to make the searching process of the best solution in a complex combinatorial optimization problem(np hard), ex : job shop scheduling problem, became more effective, in a less computational time but with no guarantee to optimum solution.In this paper, tabu search is used to solve the job shop scheduling problem consists of 3 (three) cases, which is ordering package of September, October and November with objective of minimizing makespan (Cmax). For each ordering package, there is a combination for initial solution and tabu list length. These result then compared with 4 (four) other methods using basic dispatching rules such as Shortest Processing Time (SPT), Earliest Due Date (EDD), Most Work Remaining (MWKR) dan First Come First Served (FCFS). Scheduling used Tabu Search Algorithm is sensitive for variables changes and gives makespan shorter than scheduling used by other four methods.